Fabrication of a 100 × 100 mm2 nanometer-thick graphite pellicle for extreme ultraviolet lithography by a peel-off and camphor-supported transfer approach. Issue 18 (16th August 2022) - Nam, Ki-Bong; Hu, Qicheng; Yeo, Jin-Ho; Kim, Mun Ja; Yoo, Ji-Beom
Abstract : We fabricated a non-destructive and residue-free freestanding nanometer-thick graphite (NGF) pellicle (thickness ∼ 20 nm) with a size of 100 × 100 mm 2 by developing a method using a peel-off approach combined with camphor-supported transfer. Abstract : An extreme ultraviolet (EUV) lithography pellicle is used to physically protect a mask from contaminants during the EUV exposure process and needs to have a high EUV transmittance. The EUV pellicle should be fabricated using a freestanding thin film with several tens of nanometer thickness in an area of 110 × 142 mm 2, which is a challenging task. Here, we propose a peel-off approach to directly detach the nanometer-thick graphite film (NGF)/Ni film from SiO2 /Si wafer and significantly shorten the etching time of the Ni film. Combined with the residue-damage-free transfer method that used camphor as a supporting layer, we successfully fabricated a large-area (100 × 100 mm 2 ) NGF pellicle with a thickness of ∼20 nm, and an EUV transmittance of ∼87.2%.